THE INFLUENCE OF WORK COMPETENCE AND DISCIPLINE ON ASN PERFORMANCE IN STAFFING AND HUMAN RESOURCES DEVELOPMENT AGENCY IN SAMARINDA CITY - Yurika Rahma Yanti; Joko Sabtohadi; Praja Hadi Saputra (Jurnal Scientia, 2023)
There are findings, based on the 2021-2026 strategic plan regarding low and uneven HR development in providing quality human resources and the absence of effective and efficient reform of the state civil apparatus bureaucracy. This study aims to see the effect of competence on performance, the effect of work discipline on performance and which variables most influence performance at the Personnel and Human Resources Development Agency (BKPSDM) in Samarinda City. This study used a quantitative approach with 67 samples of ASN employees. Methods of data collection using offline and online questionnaires. Data analysis in this study is multiple linear regression. The research findings show that partially and simultaneously the competence and work discipline variables have a significant effect on ASN performance at BKPSDM in Samarinda City and competency has more influence on ASN performance at BKPSDM in Samarinda City.